2018
DOI: 10.3892/mmr.2018.9478
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‑328 overexpression confers cisplatin resistance in non‑small cell lung cancer via targeting of PTEN

Abstract: Chemotherapy resistance, the molecular mechanism of which is complex and has not been fully understood, poses a major challenge in the treatment of patients with non‑small cell lung cancer (NSCLC). The dysregulation of microRNAs (miRs) has been reported to serve a pivotal role in the development of cancer and drug resistance. In the present study, reverse transcription‑quantitative polymerase chain reaction analysis revealed a significant increase in miR‑328 and a significant decrease in phosphatase and tensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
(25 reference statements)
1
16
0
1
Order By: Relevance
“…More importantly, PTEN is also involved in drug resistance in NSCLC. For instance, aberrant expression of miR-328 causes cisplatin resistance by targeting PTEN in NSCLC [36]. miR-181 mediates cisplatin resistance in NSCLC through the PTEN/PI3 K/AKT pathway [37].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, PTEN is also involved in drug resistance in NSCLC. For instance, aberrant expression of miR-328 causes cisplatin resistance by targeting PTEN in NSCLC [36]. miR-181 mediates cisplatin resistance in NSCLC through the PTEN/PI3 K/AKT pathway [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miR-328-5p was determined to be overexpressed in NSCLC tumors. This is consistent with the RT-qPCR data from a previous study of NSCLC tumors (48). Similar to the effect in NSCLC cells transfected with TPTEP1, knockdown of miR-328-5p inhibited cell proliferation and induced cell apoptosis in NSCLC cells.…”
Section: Discussionsupporting
confidence: 91%
“…42 Previous studies also identified the involvement of miR-608 and miR-328 in the development of cisplatin resistance in NSCLC. 43,44 Furthermore, some circular RNAs, such as hsa_circ_0085131, circ_0076305 and hsa_circ_0001946, have been linked with the resistance to cisplatin in NSCLC. 8,45,46 These findings urge the attempt to investigate the role of lncRNAs in cisplatin resistance in NSCLC.…”
Section: Discussionmentioning
confidence: 99%